Imaging Mass Cytometric Analysis of Postmortem Tissues Reveals Dysregulated Immune Cell and Cytokine Responses in Multiple Organs of COVID-19 Patients - Wang, Chong; Xu, Jiqian; Wang, Shaoyuan; Pan, Shangwen; Zhang, Jiancheng; Han, Yang; Huang, Muhan; Wu, Di; Yang, Qingyu; Yang, Xiaobo; Yang, Yang; Shu, Ting; et al. (Frontiers in Microbiology, 2020)
Abstract Immune dysregulation and inflammatory responses to SARS-coronavirus-2 infection are involved in the pathogenesis of coronavirus disease-2019 (COVID-19). However, little knowledge about in situ alterations of immune cells and cytokines in specific organs of COVID-19 patients. Here, we evaluated immune cells and cytokines in the lungs, intestine, liver, kidneys, and spleen, of three patients with COVID-19. Imaging mass cytometry showed that monocytes, macrophages, and dendritic cells (DCs) infiltrated into the lungs, intestine, kidneys, and liver. Moreover, in patients with COVID-19, natural killer T cells were recruited to the liver, lungs, and intestine, whereas B cells were recruited to the kidneys, lungs, and intestine. CD11b+ macrophages and CD11c+ DCs were also recruited to the lungs and intestine, accompanied by overproduction of immunosuppressive cytokine interleukin (IL)-10. However, human leukocyte antigen DR isotype expression did not colocalize in CD11b+ macrophages and CD11c+ DCs in the lungs or intestine of COVID-19 patients. In contrast, tumor necrosis factor (TNF)-α expression was higher in the lungs, intestine, liver, and kidneys, but not in the spleen, of all COVID-19 patients compared with control. Collectively, these findings suggested that IL-10 and TNF-α, as immunosuppressive and pro-inflammatory pathways, respectively, may be prognostic and could serve as therapeutic targets for COVID-19.